PENERAPAN METODE PROJECT WORK DALAM PEMBELAJARAN PRAKTIK UNTUK MENINGKATKAN KOMPETENSI PRAKTIK BODY OTOMOTIF PADA MAHASISWA PENDIDIKAN TEKNIK MESIN FKIP UNS TA 2012/2013 - Basori Basori (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2013)
This reseach aims to study how to improve the student competence by implementation of project work learning method . Specifically this research aims to study the percentage of mastery learning on automotive body practice lecture .This research used PTK ( Classroom Action Research ) and was performed two cycles . The research was conducted in the Mechanical Engineering Department at PTK UNS PTK with 7th semester students . And the student took a course automotive body practice. The number of the student was 34 person. Data was collected by a test or tests of competence . Analysis of the data used descriptive qualitative analysisThe results shows that student competence’s increase in automotive body practice learning. From two cycles , there has been an increase in from 72.85 to be 77.24 . In the second cycle to 70.01 . While the percentage of students who have not passed are also increasing . From 11.8 % to 2.9 % . In the second cycle of 0% .